Nylon material as well as preparation method and application thereof

By using a composite system of nitrogen-based and phosphorus-based flame retardant in nylon materials, combined with zinc borate and glass powder as synergistic flame retardant, the problem that nylon materials cannot be extinguished quickly when ignited at high temperatures is solved, and the demand for high flame retardant performance and environmental protection is achieved.

CN119775766AActive Publication Date: 2025-04-08GUANGZHOU SUPER DRAGON ENG PLASTICS +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411982930.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing nylon materials cannot be extinguished quickly when they are ignited at high temperatures, and traditional halogen flame retardants have environmental protection and safety risks, which cannot meet the needs of high flame retardant performance and environmental protection in new energy vehicles and other fields.

Method used

A composite material of 70%-85% nylon resin, 8%-15% nitrogen-based flame retardant, 2%-8% phosphorus-based flame retardant and 1%-8% synergistic flame retardant is used to combine zinc borate and glass powder as synergistic flame retardant to form an efficient flame retardant barrier.

Benefits of technology

It significantly increases the ignition temperature of the glow wire of the nylon material, reduces the dripping speed and dripping ignition probability, improves the flame retardant performance of the material, and meets environmental protection and safety requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221930360000041
    Figure BDA0005221930360000041
  • Figure BDA0005221930360000042
    Figure BDA0005221930360000042
  • Figure BDA0005221930360000051
    Figure BDA0005221930360000051
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and discloses a nylon material as well as a preparation method and application thereof. The nylon material is prepared from the following raw materials in percentage by mass: 70-85% of nylon resin, 8-15% of a nitrogen flame retardant, 2-8% of a phosphorus flame retardant and 1-8% of a synergistic flame retardant. According to the nylon material provided by the invention, the phosphorus-based flame retardant and the synergistic flame retardant are added into a traditional nitrogen-based flame-retardant system, so that the ignition temperature of a glowing filament of the material is increased, the dripping speed and the dripping ignition probability are reduced, and the flame-retardant property of the material is improved. The glowing filament ignition temperature of the material can reach 745 DEG C, the DSC crystallization temperature can reach 187 DEG C, the demolding effect is good, the dripping speed is low, the dripping ignition probability is low, the performance requirement of a battery assembly product on the material can be met, and the material can be used for preparing electronic connectors, battery bins, low-voltage switches, shells or power distribution system terminals of electronic and electrical equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a nylon material and a preparation method and application thereof. Background Art

[0002] With the comprehensive expansion of the new energy vehicle industry market, the demand for connectors for current distribution in its power system and electronic control system is growing rapidly. Such components require higher safety, and the material's glow wire ignition temperature is required to be higher, and it should be extinguished quickly after ignition at a higher temperature. Materials with traditional brominated flame retardants cannot meet environmental protection requirements, so it is necessary to develop flame retardant materials with high flame retardant properties and more environmentally friendly.

[0003] Nylon materials have advantages such as good processability, chemical resistance and mechanical properties, and are widely used in the market. However, nylon is a flammable material, which emits a lot of smoke and toxic gases when burned, accompanied by dripping and ignition, and cannot meet the high flame retardant requirements of home appliances and electronic appliances.

[0004] The flame retardant modification systems of nylon materials mainly include halogen flame retardant modification and halogen-free flame retardant modification. Among them, halogen flame retardant modified nylon has good flame retardant effect and simple preparation process, but it will produce a large amount of toxic halogen gas when burned, and after escaping into the air, it is easy to combine with water to form a highly corrosive liquid, which will seriously endanger human health and hinder escape from fire disasters. In comparison, halogen-free flame retardants mainly based on nitrogen and phosphorus are safer and more environmentally friendly.

[0005] The flame retardant commonly used in halogen-free flame-retardant modified nylon is melamine cyanurate (MCA) flame retardant. MCA belongs to nitrogen-based flame retardants. Its main body is a greasy powder with a certain lubricating effect. Its flame retardant mechanism mainly includes the following points: ① The molecular structure of MCA flame retardant has a large area of ​​hydrogen bond network, which has good heat resistance. When the material is thermally decomposed, it can help the nylon substrate absorb a large amount of heat and reduce the overall temperature; ② MCA flame retardant can quickly carbonize to form a dense honeycomb non-combustible carbon layer that is difficult to burn when burning. These foam-like carbon layers effectively limit the diffusion of heat and block oxygen; ③ MCA flame retardant can release nitrogen after thermal decomposition to form an inert atmosphere, dilute the surface oxygen and reduce the combustion reaction; ④ MCA halogen-free flame retardant nylon can take away heat by dripping the softened part during the combustion process.

[0006] However, nylon materials modified only with MCA still have the following defects: ① The ignition temperature of nylon glow wire is not ideal; ② MCA has poor dispersion in nylon materials, which easily leads to insufficient flame retardant properties; ③ Small molecules are easily precipitated during the injection molding process, resulting in a shortened time interval for cleaning the mold; ④ MCA will reduce the crystallization rate of nylon, resulting in a longer molding time. Summary of the invention

[0007] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a nylon material; the second purpose of the present invention is to provide a method for preparing the nylon material; the third purpose of the present invention is to provide an application of the nylon material.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] The first aspect of the present invention provides a nylon material, comprising the following raw materials in percentage by mass: 70%-85% nylon resin, 8%-15% nitrogen flame retardant, 2%-8% phosphorus flame retardant and 1%-8% synergistic flame retardant.

[0010] In the present invention, in order to solve the problem that the flame retardant effect is poor when a nitrogen-based flame retardant is used alone, a nitrogen-based flame retardant and a phosphorus-based flame retardant are used in combination. The nitrogen-based flame retardant can release nitrogen when decomposed to form an inert gas phase, reduce the oxygen concentration, and thus inhibit combustion. The phosphorus-based flame retardant can form a solid-phase and gas-phase flame-retardant barrier by releasing substances such as phosphoric acid and phosphorus pentoxide. When used in combination, the two flame retardants can complement each other's flame retardant mechanisms and improve the flame retardancy of the material.

[0011] In some embodiments of the present invention, the nylon resin is selected from at least one of polycaprolactam (nylon 6) and polyhexamethylene adipamide (nylon 66).

[0012] In some embodiments of the present invention, the nitrogen-based flame retardant includes melamine cyanurate (MCA).

[0013] In some embodiments of the present invention, the phosphorus-based flame retardant is selected from at least one of melamine pyrophosphate and zinc phytate.

[0014] In some specific embodiments of the present invention, the phosphorus-based flame retardant is a composite phosphorus-based flame retardant composed of melamine pyrophosphate and zinc phytate in any proportion.

[0015] In the present invention, the selected phosphorus flame retardants melamine pyrophosphate (melamine pyrophosphate) and zinc inositol hexaphosphate (zinc phytate) both have a high phosphorus content and can improve the flame retardancy of the material when added alone. Compared with melamine pyrophosphate, zinc inositol hexaphosphate has a higher phosphorus content. When used together with melamine pyrophosphate, the material can release more phosphoric acid components when heated, thereby improving the flame retardant efficiency of the material. In addition, zinc inositol hexaphosphate is a bio-based material and is more environmentally friendly.

[0016] In some embodiments of the present invention, the synergistic flame retardant is selected from at least one of zinc borate and glass powder.

[0017] In some embodiments of the present invention, the melting point of the glass powder is less than 800°C.

[0018] In some embodiments of the present invention, the synergistic flame retardant is a compound of zinc borate and glass powder in a mass ratio of 1:(1-5).

[0019] In the present invention, zinc borate and glass powder are added as synergistic flame retardants, which can form a dense vitrified coating on the material during combustion, block the diffusion of heat and the escape of combustible gas, and promote carbonization to improve the flame retardant efficiency.

[0020] In some embodiments of the present invention, the nylon material further comprises the following preparation raw materials: 0.1%-2% nucleating agent.

[0021] In some embodiments of the present invention, the nucleating agent is selected from talc, and at least one of calcium stearate and glyceryl monostearate.

[0022] In some embodiments of the present invention, the talc accounts for 70%-80% of the mass of the nucleating agent.

[0023] In some embodiments of the present invention, the particle size of the talc is 8000-12000 mesh.

[0024] In the present invention, the nucleating agent includes an organic nucleating agent and an inorganic nucleating agent, and the inorganic nucleating agent accounts for a larger proportion. When nano-grade talc is used as the nucleating agent, compared with the organic nucleating agent, it can reduce costs and resource dependence, improve the crystallinity of the material, reduce the molding cycle of the material, and improve the molding efficiency; adding calcium stearate and / or glyceryl monostearate organic nucleating agents can improve the dispersibility of talc during the processing process and improve the demolding effect of the material during injection molding.

[0025] In some embodiments of the present invention, the nylon material further comprises the following preparation raw materials: 0.1%-1% antioxidant and 0.01%-0.2% surface modifier.

[0026] In some embodiments of the present invention, the antioxidant is selected from at least one of hindered phenol antioxidants, thioester antioxidants, and phosphite antioxidants.

[0027] In some specific embodiments of the present invention, the antioxidant is a compound of a hindered phenol antioxidant and a phosphite antioxidant.

[0028] In some specific embodiments of the present invention, the mass ratio of the hindered phenol antioxidant to the phosphite antioxidant is (2-3):1.

[0029] In some specific embodiments of the present invention, the hindered phenol antioxidant is selected from at least one of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine (antioxidant 1098), 2,6-di-tert-butyl-p-methylphenol (BHT), β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1076), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (antioxidant 1010), and triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate] (antioxidant 245).

[0030] In some specific embodiments of the present invention, the phosphite antioxidant is selected from at least one of tris[2,4-di-tert-butylphenyl]phosphite (antioxidant 168), bisphenol A phosphite, triphenyl phosphite (TPP), and diphenyl isooctyl phosphite (ODPP).

[0031] In some embodiments of the present invention, the surfactant is selected from at least one of an aminosilane coupling agent and an epoxysilane coupling agent.

[0032] In some specific embodiments of the present invention, the surfactant is selected from at least one of γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.

[0033] In some embodiments of the present invention, the nylon material comprises the following raw materials by mass percentage:

[0034] Nylon resin 70%-85%;

[0035] Nitrogen flame retardant 8%-15%;

[0036] Phosphorus flame retardant 2%-8%;

[0037]

[0038] In some specific embodiments of the present invention, the nylon material includes the following preparation raw materials by mass percentage:

[0039]

[0040] In some specific embodiments of the present invention, the density of the nylon material is 1.1-1.3 g / cm 3 .

[0041] In some specific embodiments of the present invention, the glow-wire ignition temperature of the nylon material is ≥725°C.

[0042] The second aspect of the present invention provides a method for preparing the nylon material according to the first aspect of the present invention, comprising the following steps:

[0043] The prepared raw materials except the phosphorus flame retardant are mixed to obtain a premix; the premix is ​​added from the main feeding port of a twin-screw extruder to perform melt mixing; the phosphorus flame retardant is added from the side feeding port of the twin-screw extruder, melt extruded and granulated to obtain the nylon material.

[0044] In some embodiments of the present invention, the preparation method specifically comprises the following steps:

[0045] Firstly, nylon resin, nucleating agent, synergistic flame retardant and surface modifier are mixed, and then nitrogen flame retardant and antioxidant are added to mix to obtain a premix; the premix is ​​added from the main feeding port of a twin-screw extruder to perform melt mixing; the phosphorus flame retardant is added from the side feeding port of the twin-screw extruder, and melt extrusion granulation is performed to obtain the nylon material.

[0046] In some embodiments of the present invention, the mixing speed of the premix is ​​800-1500 r / min.

[0047] In some embodiments of the present invention, the mixing temperature of the premix is ​​40-50°C.

[0048] In some embodiments of the present invention, the mixing time of the premix is ​​3-5 min.

[0049] In some embodiments of the present invention, the temperatures of the barrels of the twin-screw extruder from the hopper to the die are: first barrel: 170-190°C, second barrel: 220-240°C, third barrel: 230-250°C, fourth barrel: 240-260°C, fifth barrel: 250-270°C, sixth barrel: 250-270°C, seventh barrel: 220-240°C, eighth barrel: 210-230°C, ninth barrel: 210-230°C.

[0050] In some embodiments of the present invention, the side feed port is located in the fifth barrel section of the twin-screw extruder.

[0051] In some embodiments of the present invention, the head temperature of the twin-screw extruder is 240-260°C.

[0052] In some embodiments of the present invention, the screw speed of the twin-screw extruder is 300-600 r / min.

[0053] In the present invention, in view of the poor temperature resistance of phosphorus-based flame retardants, they are added from the side feeding port during the preparation process, which reduces the degradation loss and unstable foaming during the processing, maximizes the role of the flame retardant, and improves the flame retardant properties of the material.

[0054] The third aspect of the present invention provides the use of the nylon material described in the first aspect of the present invention in the preparation of battery component products.

[0055] In some embodiments of the present invention, the battery assembly product includes electronic connectors, battery compartments, low-voltage switches, casings, and distribution system terminals of new energy electric vehicles and / or other electronic and electrical equipment.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] 1) The nylon material provided by the present invention adds a phosphorus-based flame retardant and a synergistic flame retardant to the traditional nitrogen-based flame retardant system, so that the glow-wire ignition temperature of the material is increased, the dripping speed and the probability of dripping ignition are reduced, and the flame retardant performance of the material is improved;

[0058] 2) The nylon material provided by the present invention is added with a nucleating agent, so that the crystallization temperature of the material is increased, the molding cycle is shortened, and the demoulding effect is improved;

[0059] 3) The preparation method of the nylon material provided by the present invention has simple steps and mild process conditions, and adopts the side feeding method of the phosphorus-based flame retardant, which reduces the degradation failure and foaming decomposition of the flame retardant during the processing, and ensures the efficacy of the flame retardant;

[0060] 4) The nylon material provided by the present invention has a glow-wire ignition temperature of up to 745°C and a DSC crystallization temperature of up to 187°C, has a good demolding effect, a slow dripping speed, and a low probability of dripping ignition, and can meet the performance requirements of battery component products for materials, and can be used in the preparation of electronic connectors, battery compartments, low-voltage switches, housings or distribution system terminals of electronic and electrical equipment. DETAILED DESCRIPTION

[0061] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0062] The raw material information used in the following examples and comparative examples is shown in Table 1 below:

[0063] Table 1 Information of raw materials used in the examples and comparative examples

[0064]

[0065]

[0066] Example 1

[0067] This example prepares a nylon material, and the raw materials are shown in Table 2:

[0068] Table 2 Raw material composition of nylon material in Example 1

[0069]

[0070] The preparation method of nylon material comprises the following steps:

[0071] At 60°C, nylon resin, synergistic flame retardant and surface modifier were first mixed at a high speed of 1000 r / min for 5 minutes, and then nitrogen flame retardant and antioxidant were added and mixed for 3 minutes to obtain a premix;

[0072] The premix is ​​added from the main feeding port of the twin-screw extruder for melt mixing, and the phosphorus flame retardant is added from the side feeding port of the twin-screw extruder for melt extrusion and granulation to obtain a nylon material.

[0073] Among them, the side feeding port is located at the fifth section of the barrel of the twin-screw extruder; the temperatures of each section of the barrel of the twin-screw extruder from the hopper to the die head are: the first section of the barrel: 180°C, the second section of the barrel: 230°C, the third section of the barrel: 245°C, the fourth section of the barrel: 250°C, the fifth section of the barrel: 260°C, the sixth section of the barrel: 250°C, the seventh section of the barrel: 230°C, the eighth section of the barrel: 220°C, the ninth section of the barrel: 220°C; the head temperature is 250°C, and the screw speed is 450r / min.

[0074] Example 2

[0075] This example prepares a nylon material, and the raw materials are shown in Table 3:

[0076] Table 3 Raw material composition of nylon material in Example 2

[0077]

[0078] The preparation method of nylon material comprises the following steps:

[0079] At 60°C, nylon resin, synergistic flame retardant and surface modifier were first mixed at a high speed of 1000 r / min for 5 minutes, and then nitrogen flame retardant and antioxidant were added and mixed for 3 minutes to obtain a premix;

[0080] The premix is ​​added from the main feeding port of the twin-screw extruder for melt mixing, and the phosphorus flame retardant is added from the side feeding port of the twin-screw extruder for melt extrusion and granulation to obtain a nylon material.

[0081] Among them, the side feeding port is located at the fifth section of the barrel of the twin-screw extruder; the temperatures of each section of the barrel of the twin-screw extruder from the hopper to the die head are: the first section of the barrel: 180°C, the second section of the barrel: 230°C, the third section of the barrel: 245°C, the fourth section of the barrel: 250°C, the fifth section of the barrel: 260°C, the sixth section of the barrel: 250°C, the seventh section of the barrel: 230°C, the eighth section of the barrel: 220°C, the ninth section of the barrel: 220°C; the head temperature is 250°C, and the screw speed is 450r / min.

[0082] Example 3

[0083] This example prepares a nylon material, and the raw materials are shown in Table 4:

[0084] Table 4 Raw material composition of nylon material in Example 3

[0085]

[0086]

[0087] The preparation method of nylon material comprises the following steps:

[0088] At 60°C, nylon resin, synergistic flame retardant and surface modifier were first mixed at a high speed of 1000 r / min for 5 minutes, and then nitrogen flame retardant and antioxidant were added and mixed for 3 minutes to obtain a premix;

[0089] The premix is ​​added from the main feeding port of the twin-screw extruder for melt mixing, and the phosphorus flame retardant is added from the side feeding port of the twin-screw extruder for melt extrusion and granulation to obtain a nylon material.

[0090] Among them, the side feeding port is located at the fifth section of the barrel of the twin-screw extruder; the temperatures of each section of the barrel of the twin-screw extruder from the hopper to the die head are: the first section of the barrel: 180°C, the second section of the barrel: 230°C, the third section of the barrel: 245°C, the fourth section of the barrel: 250°C, the fifth section of the barrel: 260°C, the sixth section of the barrel: 250°C, the seventh section of the barrel: 230°C, the eighth section of the barrel: 220°C, the ninth section of the barrel: 220°C; the head temperature is 250°C, and the screw speed is 450r / min.

[0091] Example 4

[0092] This example prepares a nylon material, and the raw materials are shown in Table 5:

[0093] Table 5 Raw material composition of nylon material in Example 4

[0094]

[0095] The preparation method of nylon material comprises the following steps:

[0096] At 60°C, nylon resin, synergistic flame retardant and surface modifier were first mixed at a high speed of 1000 r / min for 5 minutes, and then nitrogen flame retardant and antioxidant were added and mixed for 3 minutes to obtain a premix;

[0097] The premix is ​​added from the main feeding port of the twin-screw extruder for melt mixing, and the phosphorus flame retardant is added from the side feeding port of the twin-screw extruder for melt extrusion and granulation to obtain a nylon material.

[0098] Among them, the side feeding port is located at the fifth section of the barrel of the twin-screw extruder; the temperatures of each section of the barrel of the twin-screw extruder from the hopper to the die head are: the first section of the barrel: 180°C, the second section of the barrel: 230°C, the third section of the barrel: 245°C, the fourth section of the barrel: 250°C, the fifth section of the barrel: 260°C, the sixth section of the barrel: 250°C, the seventh section of the barrel: 230°C, the eighth section of the barrel: 220°C, the ninth section of the barrel: 220°C; the head temperature is 250°C, and the screw speed is 450r / min.

[0099] Example 5

[0100] This example prepares a nylon material, and the raw materials are shown in Table 6:

[0101] Table 6 Raw material composition of nylon material in Example 5

[0102]

[0103] The preparation method of nylon material comprises the following steps:

[0104] At 60°C, nylon resin, synergistic flame retardant and surface modifier were first mixed at a high speed of 1000 r / min for 5 minutes, and then nitrogen flame retardant and antioxidant were added and mixed for 3 minutes to obtain a premix;

[0105] The premix is ​​added from the main feeding port of the twin-screw extruder for melt mixing, and the phosphorus flame retardant is added from the side feeding port of the twin-screw extruder for melt extrusion and granulation to obtain a nylon material.

[0106] Among them, the side feeding port is located at the fifth section of the barrel of the twin-screw extruder; the temperatures of each section of the barrel of the twin-screw extruder from the hopper to the die head are: the first section of the barrel: 180°C, the second section of the barrel: 230°C, the third section of the barrel: 245°C, the fourth section of the barrel: 250°C, the fifth section of the barrel: 260°C, the sixth section of the barrel: 250°C, the seventh section of the barrel: 230°C, the eighth section of the barrel: 220°C, the ninth section of the barrel: 220°C; the head temperature is 250°C, and the screw speed is 450r / min.

[0107] Example 6

[0108] This example prepares a nylon material, and the raw materials are shown in Table 7:

[0109] Table 7 Raw material composition of nylon material in Example 6

[0110]

[0111] The preparation method of nylon material comprises the following steps:

[0112] At 60°C, nylon resin, nucleating agent, synergistic flame retardant and surface modifier were first mixed at a high speed of 1000 r / min for 5 minutes, and then nitrogen flame retardant and antioxidant were added and mixed for 3 minutes to obtain a premix;

[0113] The premix is ​​added from the main feeding port of the twin-screw extruder for melt mixing, and the phosphorus flame retardant is added from the side feeding port of the twin-screw extruder for melt extrusion and granulation to obtain a nylon material.

[0114] Among them, the side feeding port is located at the fifth section of the barrel of the twin-screw extruder; the temperatures of each section of the barrel of the twin-screw extruder from the hopper to the die head are: the first section of the barrel: 180°C, the second section of the barrel: 230°C, the third section of the barrel: 245°C, the fourth section of the barrel: 250°C, the fifth section of the barrel: 260°C, the sixth section of the barrel: 250°C, the seventh section of the barrel: 230°C, the eighth section of the barrel: 220°C, the ninth section of the barrel: 220°C; the head temperature is 250°C, and the screw speed is 450r / min.

[0115] Comparative Example 1

[0116] This comparative example prepares a nylon material, and the raw materials are shown in Table 8:

[0117] Table 8 Raw material composition of nylon material in comparative example 1

[0118]

[0119]

[0120] The preparation method of nylon material comprises the following steps:

[0121] At 60°C, nylon resin and surface modifier were first mixed at a high speed of 1000 r / min for 5 minutes, and then nitrogen flame retardant and antioxidant were added and mixed for 3 minutes to obtain a premix;

[0122] The premix is ​​added from the main feed port of the twin-screw extruder, melt-mixed, extruded and granulated to obtain a nylon material.

[0123] Among them, the temperatures of each section of the barrel of the twin-screw extruder from the hopper to the die head are: the first section barrel: 180°C, the second section barrel: 230°C, the third section barrel: 245°C, the fourth section barrel: 250°C, the fifth section barrel: 260°C, the sixth section barrel: 250°C, the seventh section barrel: 230°C, the eighth section barrel: 220°C, the ninth section barrel: 220°C; the head temperature is 250°C, and the screw speed is 450r / min.

[0124] Comparative Example 2

[0125] This comparative example prepares a nylon material, and the raw materials are shown in Table 9:

[0126] Table 9 Raw material composition of nylon material in comparative example 2

[0127]

[0128] The preparation method of nylon material comprises the following steps:

[0129] At 60°C, nylon resin and surface modifier were first mixed at a high speed of 1000 r / min for 5 minutes, and then nitrogen flame retardant and antioxidant were added and mixed for 3 minutes to obtain a premix;

[0130] The premix is ​​added from the main feeding port of the twin-screw extruder for melt mixing, and the phosphorus flame retardant is added from the side feeding port of the twin-screw extruder for melt extrusion and granulation to obtain a nylon material.

[0131] Among them, the side feeding port is located at the fifth section of the barrel of the twin-screw extruder; the temperatures of each section of the barrel of the twin-screw extruder from the hopper to the die head are: the first section of the barrel: 180°C, the second section of the barrel: 230°C, the third section of the barrel: 245°C, the fourth section of the barrel: 250°C, the fifth section of the barrel: 260°C, the sixth section of the barrel: 250°C, the seventh section of the barrel: 230°C, the eighth section of the barrel: 220°C, the ninth section of the barrel: 220°C; the head temperature is 250°C, and the screw speed is 450r / min.

[0132] Comparative Example 3

[0133] This comparative example prepares a nylon material, and the raw materials are shown in Table 10:

[0134] Table 10 Raw material composition of nylon material in comparative example 3

[0135]

[0136] The preparation method of nylon material comprises the following steps:

[0137] At 60°C, nylon resin and surface modifier were first mixed at a high speed of 1000 r / min for 5 minutes, and then nitrogen flame retardant and antioxidant were added and mixed for 3 minutes to obtain a premix;

[0138] The premix is ​​added from the main feeding port of the twin-screw extruder for melt mixing, and the phosphorus flame retardant is added from the side feeding port of the twin-screw extruder for melt extrusion and granulation to obtain a nylon material.

[0139] Among them, the side feeding port is located at the fifth section of the barrel of the twin-screw extruder; the temperatures of each section of the barrel of the twin-screw extruder from the hopper to the die head are: the first section of the barrel: 180°C, the second section of the barrel: 230°C, the third section of the barrel: 245°C, the fourth section of the barrel: 250°C, the fifth section of the barrel: 260°C, the sixth section of the barrel: 250°C, the seventh section of the barrel: 230°C, the eighth section of the barrel: 220°C, the ninth section of the barrel: 220°C; the head temperature is 250°C, and the screw speed is 450r / min.

[0140] Comparative Example 4

[0141] This comparative example prepares a nylon material, and the raw materials are shown in Table 11:

[0142] Table 11 Raw material composition of nylon material in comparative example 4

[0143]

[0144] The preparation method of nylon material comprises the following steps:

[0145] At 60°C, nylon resin and surface modifier were first mixed at a high speed of 1000 r / min for 5 minutes, and then nitrogen flame retardant and antioxidant were added and mixed for 3 minutes to obtain a premix;

[0146] The premix is ​​added from the main feeding port of the twin-screw extruder for melt mixing, and the phosphorus flame retardant is added from the side feeding port of the twin-screw extruder for melt extrusion and granulation to obtain a nylon material.

[0147] Among them, the side feeding port is located at the fifth section of the barrel of the twin-screw extruder; the temperatures of each section of the barrel of the twin-screw extruder from the hopper to the die head are: the first section of the barrel: 180°C, the second section of the barrel: 230°C, the third section of the barrel: 245°C, the fourth section of the barrel: 250°C, the fifth section of the barrel: 260°C, the sixth section of the barrel: 250°C, the seventh section of the barrel: 230°C, the eighth section of the barrel: 220°C, the ninth section of the barrel: 220°C; the head temperature is 250°C, and the screw speed is 450r / min.

[0148] Comparative Example 5

[0149] This comparative example prepares a nylon material, and the raw materials are shown in Table 12:

[0150] Table 12 Raw material composition of nylon material in comparative example 5

[0151]

[0152] The preparation method of nylon material comprises the following steps:

[0153] At 60°C, nylon resin and surface modifier were first mixed at a high speed of 1000 r / min for 5 minutes, and then nitrogen flame retardant and antioxidant were added and mixed for 3 minutes to obtain a premix;

[0154] The premix is ​​added from the main feeding port of the twin-screw extruder for melt mixing, and the phosphorus flame retardant is added from the main feeding port of the twin-screw extruder for melt extrusion and granulation to obtain a nylon material.

[0155] Among them, the temperatures of each section of the barrel of the twin-screw extruder from the hopper to the die head are: the first section barrel: 180°C, the second section barrel: 230°C, the third section barrel: 245°C, the fourth section barrel: 250°C, the fifth section barrel: 260°C, the sixth section barrel: 250°C, the seventh section barrel: 230°C, the eighth section barrel: 220°C, the ninth section barrel: 220°C; the head temperature is 250°C, and the screw speed is 450r / min.

[0156] Performance Testing

[0157] The nylon materials prepared in Examples 1-6 and Comparative Examples 1-5 were subjected to performance tests, and the test items and standards were as follows:

[0158] 1. Density: Tested in accordance with ISO 1183-1-2019 "Determination of density of plastics, non-foamed plastics";

[0159] 2. DSC crystallization temperature: Tested in accordance with ISO 11357-1:2023 "Plastics. Differential Scanning Calorimetry (DSC)";

[0160] 3. Glow wire ignition temperature: Tested in accordance with GB / T 5169.10-2017 "Basic test methods for glow wires";

[0161] 4. Demolding effect: Use a standard spline mold to make samples to visually inspect the demoulding effect. The more “+” there are, the better the demoulding effect.

[0162] 5. Dripping speed: visual inspection, the more “+” there are, the earlier the first drop of melt will drip;

[0163] 6. Dripping ignition probability: take the average value of the dripping ignition probability of 50 UL94 vertical burning tests.

[0164] Table 13 Performance test results of nylon materials in Examples 1-6 and Comparative Examples 1-5

[0165]

[0166] Table 13 shows the performance test results of the nylon materials in Examples 1-6 and Comparative Examples 1-5. It can be seen from Table 13 that the nylon material prepared in Comparative Example 1, only the nitrogen flame retardant MCA is added alone, the glow-wire ignition temperature of the material is only 705°C, demoulding is difficult, the melt drips quickly, and dripping ignition is easy; Comparative Examples 2 and Comparative Examples 3, on the basis of Comparative Example 1, add melamine pyrophosphate or zinc inositol hexaphosphate as a phosphorus flame retardant, the glow-wire ignition temperature of the nylon material is increased to 715°C and 720°C, respectively, and the probability of dripping ignition is reduced to 96%, respectively. and 94%, indicating that adding phosphorus flame retardants to the nitrogen flame retardant system can improve the flame retardant effect to a certain extent, but the crystallization temperature is not improved at this time; in Comparative Example 4, melamine pyrophosphate and zinc inositol hexaphosphate are added as phosphorus flame retardants at the same time, and the probability of dripping ignition is further reduced to 90%; the difference between Comparative Example 5 and Comparative Example 4 is that the phosphorus flame retardant is added from the main feeding port of the twin-screw extruder, and the phosphorus flame retardant undergoes a long processing time, which makes it easy to foam and decompose, thereby reducing the flame retardant efficiency. The preparation method of the side-feed phosphorus flame retardant is obviously better.

[0167] In Example 1, anhydrous zinc borate is added as a synergistic flame retardant on the basis of Comparative Example 4. It can be seen that the glow-wire ignition temperature of the nylon material is significantly increased to 740°C, and the dripping speed and the probability of dripping ignition are reduced; the difference between Example 2 and Example 1 is that the glass powder with a melting point of 650°C is used instead of anhydrous zinc borate as a synergistic flame retardant, and it is found that the purpose of reducing the dripping speed and the probability of dripping ignition can also be achieved. This is because the addition of the flame retardant synergist generates a high-temperature dense glass-like layer, which blocks the escape of combustible gases and heat erosion, and effectively improves the flame retardant effect of the material; the difference between Example 3 and Example 2 is that the glass powder with a melting point of 650°C is replaced by glass powder with a melting point of 800°C, and it is found that the dripping of the material is significantly affected. The effect leads to unstable flame retardant performance. Therefore, when glass powder is used as a flame retardant synergist, its melting point should be lower than 800°C; the difference between Example 4 and Example 2 is that the amount of glass powder with a melting point of 650°C is increased, and it is found that the dripping effect of the MCA flame retardant system is seriously affected, resulting in poor flame retardant stability; the difference between Example 5 and Example 2 is that anhydrous zinc borate and glass powder with a melting point of 650°C are added as synergistic flame retardants at the same time. It can be seen that the glow-wire ignition temperature of the material is increased to 745°C, the demoulding effect is improved, and the dripping speed and the probability of dripping ignition are reduced; Example 6 adds a nucleating agent on the basis of Example 5, and it is found that the crystallization temperature of the material is significantly increased, so that the material molding cycle is shortened and the demoulding effect is optimal.

Claims

1. A nylon material, characterized in that: The preparation material comprises the following raw materials in percentage by mass: 70%-85% of nylon resin, 8%-15% of nitrogen flame retardant, 2%-8% of phosphorus flame retardant and 1%-8% of synergistic flame retardant.

2. The nylon material according to claim 1, characterized in that: The nitrogen-based flame retardant includes melamine cyanurate; And / or, the phosphorus-based flame retardant is selected from at least one of melamine pyrophosphate and zinc phytate.

3. The nylon material according to claim 1, characterized in that: The synergistic flame retardant is selected from at least one of zinc borate and glass powder.

4. The nylon material according to claim 3, characterized in that: The synergistic flame retardant is a compound of zinc borate and glass powder in a mass ratio of 1:(1-5).

5. The nylon material according to claim 1, characterized in that: Calculated by mass percentage, the nylon material also includes the following preparation raw materials: 0.1%-2% nucleating agent.

6. The nylon material according to claim 5, characterized in that: The nucleating agent is selected from talc, and at least one of calcium stearate and glyceryl monostearate.

7. The nylon material according to claim 1, characterized in that: Calculated by mass percentage, the nylon material also includes the following preparation raw materials: 0.1%-1% antioxidant and 0.01%-0.2% surface modifier.

8. The method for preparing the nylon material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The prepared raw materials except the phosphorus flame retardant are mixed to obtain a premix; the premix is ​​added from the main feeding port of a twin-screw extruder to perform melt mixing; the phosphorus flame retardant is added from the side feeding port of the twin-screw extruder, melt extruded and granulated to obtain the nylon material.

9. The preparation method according to claim 8, characterized in that: The temperature of each section of the twin-screw extruder from the hopper to the die head is: the first section of the barrel: 170-190°C, the second section of the barrel: 220-240°C, the third section of the barrel: 230-250℃, the fourth section cylinder: 240-260℃, the fifth section cylinder: 250-270℃, the sixth section cylinder: 250-270℃, the seventh section cylinder: 220-240℃, the eighth section cylinder: 210-230℃, the ninth section cylinder: 210-230℃; And / or, the side feeding port is located at the fifth barrel section of the twin-screw extruder.

10. Use of the nylon material according to any one of claims 1 to 7 in the preparation of battery component products.

Citation Information

Patent Citations

  • Heat and flame resistant nylon composite

    CN101735601A

  • Low-melting glass, resin composition comprising same, and resin molded article

    CN102186786A

  • Halogen-free flame retardant polypropylene composite material with cold resistance and rigidness-toughness balance and preparation method of halogen-free flame retardant polypropylene composite material

    CN108117694A

  • Flame-resistant bio-based PA56 composite material, and preparation method thereof

    CN110054888A

  • Low-smoke halogen-free flame-retardant polyolefin cable material and preparation method thereof

    CN111286111A